2017
DOI: 10.1097/mao.0000000000001524
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Directional Microphones in Bilateral/Bimodal Cochlear Implant Users—Impact of Spatial and Temporal Noise Characteristics

Abstract: The absence of the glimpsing effect in CI users was reaffirmed in the present study. Although very effective in single noise source conditions, the beneficial impact of beamforming algorithms in multiple noise source conditions is poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 16 publications
5
39
0
6
Order By: Relevance
“…Spatial release from masking is thought to be due to a combination of both head shadow and binaural unmasking of speech, depending on the spectral and temporal characteristics of the signal and distracter(s) as well as the spatial location of signal and distracter(s). Research has shown that both bimodal and bilateral CI users derive benefit from spatial release from masking with similar degrees of benefit (e.g., Gifford et al, 2014;Weissgerber et al, 2017).…”
Section: Bimodal Hearing Versus Bilateral Cochlear Implantsmentioning
confidence: 99%
“…Spatial release from masking is thought to be due to a combination of both head shadow and binaural unmasking of speech, depending on the spectral and temporal characteristics of the signal and distracter(s) as well as the spatial location of signal and distracter(s). Research has shown that both bimodal and bilateral CI users derive benefit from spatial release from masking with similar degrees of benefit (e.g., Gifford et al, 2014;Weissgerber et al, 2017).…”
Section: Bimodal Hearing Versus Bilateral Cochlear Implantsmentioning
confidence: 99%
“…Clinical routine outcomes consist of CI- and HA-aided speech comprehension in quiet and noise. In research studies, performance in audiometric tests shows substantial dependence on the type of speech material, on the nature of noise confounders, and on spatial distribution of speech and noise sources ( 8 10 ). Furthermore, during audiometric tests pronunciation is clear, spectro-temporal characteristics and location of the speaker as well as noise type are static and thus predictable, and predictability increases the performance of CI-patients.…”
Section: Introductionmentioning
confidence: 99%
“…Speech perception in noise in free-field conditions was assessed with Oldenburg Sentence Test in Multi-Source Noise Field (OLSA MSNF) condition [6,26]. Speech signal was presented from front (0°) with a distance of 1.75 m to the listening position.…”
Section: Methodsmentioning
confidence: 99%
“…The order of test lists was randomized. Further details and normative data for the setup are given in [26].…”
Section: Methodsmentioning
confidence: 99%